Microbial phenolic metabolites 3-(3′,4′-dihydroxyphenyl)propanoic acid and 3′,4′-dihydroxyphenylacetic acid prevent obesity in mice fed with high-fat diet - Wanbing Chen; Ruonan Liu; Xiaoling Zhu; Qun Lu; Hong Yang; Rui Liu (Food Science and Human Wellness)
Obesity is associated with numerous metabolic disorders, and dietary polyphenols have been confirmed to have beneficial effects on the metabolism in obesity. However, the effect of 3-(3′,4′-dihydroxyphenyl)propanoic acid (DHPA) and 3′,4′-dihydroxyphenylacetic acid (DHAA), two main metabolites of dietary polyphenols, on obesity remains poorly understood. In this study, DHPA and DHAA were found to alleviate obesity, as well as regulate insulin resistance, lipid metabolism, and oxidative stress response in high-fat diet (HFD) mice. Surprisingly, the 16S rRNA sequencing and UHPLC-Q-TOF/MS demonstrated that DHPA and DHAA only slightly disturbed the intestinal microbiome, but significantly altered the urine metabolome of HFD mice mainly by regulating pentose and glucuronate interconversion, tyrosine metabolism, pentose phosphate and tricarboxylic acid (TCA) cycle as indicated by metabolic pathway analysis based on Kyoto Encyclopedia of Genes and Genomes (KEGG) database. Correlation analysis revealed that the differential metabolites are strongly associated with body weight, blood glucose, insulin level, and superoxide dismutase (SOD) enzyme activity. Our results revealed that DHPA and DHAA exert their anti-obesity effect by regulating important metabolites in the glucose, lipid and tyrosine metabolism pathways.